Foundations of Infinitesimal Calculus - Keisler, H. Jerome (Boston: Prindle, Weber & Schmidt, 1976)
The purpose of this monograph is to make infinitesimals available to mathematicians and students. The infinitesimals provided the intuition for the original development of the calculus and gives proofs of theorems whenever it is appropriate.
Includes index.
ne 5/03/2018
Loan
Keywords: Calculus